TINJAUAN YURIDIS POLIGAMI DALAM PERSPEKTIF HUKUM ISLAM DI SAMARINDA - Febriyama Harnung (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTPolygamy is a series of the word “Poly” and “gamein”  meaning many marriages, wives and if the intention is understood from the above words became legitimate to realize that the meaning of polygamy is a lote marriage and could be in an unlimited amount. Polygamy has meaning marriage is more than one with restrictions generally permissible only up to four.Methodological perspective, the adoption of laws on polygamy will be made on the relevant icenses through religious courts, as evidenced permit of wive or wives are meant to realize the benefit of which is the realization of dream aims and purposes of marriage, that household eternal and based on love an affection.Keywords : polygamy, marriage